Evaluation of eslicarbazepine for its antidiuretic effect in albino wistar rats - AM, Satish; Sibgatullah, Mohammed; Subedee, Lokraj; Kumar, Shashi; Salma, Umme; Gupta, Varun (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Diabetes insipidus is characterized by polyuria, polydipsia with hyposthenuria, causing dehydration and hypernatremia if the patient is deprived of water. Vasopressin analogues and drugs causing water retention are used in this condition. The aim of the present study was to evaluate the antidiuretic effect of eslicarbazepine in albino rats. Methods: The animals were divided into 3 groups each containing 6 animals. The first group was constituted by the control group which received distilled water. The second was the standard group which received vasopressin. The third group was constituted by the test group which received the test drug eslicarbazepine. The test drug was given for a period of 5 days. On 5th day, one hour after administration of respective drugs in different groups, diuresis was induced in all groups of animals by Furosemide after they were loaded with normal saline after overnight fasting. The volume of urine collected was measured at the end of 5 hours from each of the group along with sodium, potassium and chloride concentrations. Results: There was significant water retention and urine was concentrated in the test group which received eslicarbazepine when compared to the control group. Conclusions: Eslicarbazepine has significant water retaining capacity in albino wistar rats. Further evaluation is required before using it in diabetes insipidus.